A novel phase congruency based algorithm for online data reduction in ambulatory EEG systems - Logesparan,L; Rodriguez-Villegas,E (IEEE Transactions on Biomedical Engineering, 2011)
Abstract—Real signals are often corrupted by noise with a power spectrum variable over time. In applications involving these signals, it is expected that dynamically estimating and correcting for this noise would increase the amount of useful information extracted from the signal. One such application is scalp EEG monitoring in epilepsy, where electrical activity generated by cranio-facial muscles obscure the measured brainwaves. This paper presents a data selection algorithm based on phase congruency to identify interictal spikes from background EEG; together with a novel statistical method that allows a more comprehensive trade-off based quantitative comparison of two algorithms which have been tested at a fixed threshold in the same database. Here, traditional phase congruency has been modified to incorporate a dynamic estimate of muscle activity present in the input scalp EEG signal. The proposed algorithmachieves 50% data reduction whilst detecting more than 80% of interictal spikes. This represents a significant improvement overthe state-of-the-art denoising method for phase congruency.